Integration of Communication Based Learning Media in Distance Learning in Higher Education - Juandana Kawuladini Putra; Bayu Purwo Adhi (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study aims to examine the application of communication based learning media in distance learning in universities, especially in communication study programs. Using a qualitative approach, this study collected data through semi-structured interviews involving 5 lecturers and 20 students at Nugroho Doctoral University, Magetan Regency, in the 2025/2026 academic year. The results of the study show that communication-based learning media, such as Google Classroom, Zoom, and WhatsApp, can increase interaction between lecturers and students and provide flexibility in learning. However, the main challenge faced is limited internet access, which affects smooth learning, as well as technological skills that need to be improved for both lecturers and students. The key contribution of this study is the identification of critical factors such as technological readiness and infrastructure limitations that influence the effective use of communication-based learning media in distance learning. The implication of this research is the need to improve technological infrastructure in universities as well as continuous training for lecturers and students to make optimal use of communication-based learning media. This will strengthen the success of distance learning, make it more inclusive and effective, and support the development of higher education in the digital age.